SAT0072 Ultrasound Is Associated with Late Phases Preceding The Clinical Onset of Rheumatoid Arthritis in Individuals Genetically at Risk. (15th July 2016) - Brulhart, L.; Alpizar-Rodriguez, D.; Zufferey, P.; Bas, S.; Gascon, D.; Lamacchia, C.; Roux-Lombard, P.; Ciubotariu, E.; Nissen, M.J.; Gabay, C.; Finckh, A.
Abstract : Background: Identifying pre-clinical phases of rheumatoid arthritis (RA) is challenging. Musculoskeletal ultrasound (US) is more sensitive than clinical assessment for the detection of synovitis. US abnormalities have been associated with subsequent joint inflammation in patients with anti-citrullinated peptide antibodies (ACPA) without clinical synovitis (SJ) 1 . Objectives: To identify US abnormalities associated with the recognized phases of RA development 2 in individuals at increased risk for RA. Methods: This is a nested cohort study within an ongoing prospective study of individuals genetically at risk of developing RA, namely first degree relatives of patients with RA (FDR). Individuals without clinical evidence of RA were enrolled, and then followed-up yearly. We included in this analysis all individuals with available ACPA status (anti-CCP 2, 3.0, or 3.1) and US assessment. The US examination was conducted according to the validated SONAR score 3 and performed by US trained rheumatologists blinded to clinical and biological data. According to previous publications 4, inflammatory activity on US (active US) was defined as a Bmode score ≥9 and at least one synovitis of grade 2 or 3, or a Doppler score ≥2. We used logistic regression to analyze univariable and multivariable associations between US findings and specific phases preceding RA development and other patient characteristics. Results: A total of 269 FDRs were analyzed, of which 97 (36%) had an active US as defined above. Individuals with an active US tended to be older (years median (IQR): 51 (41–59) vs 47 (35–57), OR: 1.0, 95% CI: 1.0–1.0, p<0.05), with no difference in sex, body mass index and tobacco smoking. In univariable analyses, there was a strong correlation between an active US and the presence of 'unclassified arthritis' (≥1 SJ on physical examination) (OR:2.6, 95% CI:1.4–4.9). No association was demonstrated with genetic risk factors (presence of shared epitope), systemic autoimmunity (ACPA positivity) or self reported symptoms in the absence of arthralgia or SJ (Table 1 ). In the multivariable analyses, the relation between US and 'unclassified arthritis' remained significant (OR:2.4, 95% CI:1.3–4.5). Conclusions: In individuals at risk of RA, active US was strongly associated with the presence of "unclassified arthritis". There was no association between US findings and earlier identified phases of RA development. These data suggest that in individuals at increased risk for RA, without obvious disease, US may identify imminent RA. These findings support the usefulness of US in a screening strategy for imminent RA. References: Nam JL et al. Ann Rheum Dis. 2016 Jan 22. Gerlag DM et al. Ann Rheum Dis. 2012 May;71(5):638–41. 3.Zufferey P. Joint Bone Spine 2014;81(3):222–7. 4.Zufferey P et al. Swiss Med Wkly.2013;143. Disclosure of Interest: None declared